Research on stitching method of satellite visual navigation image - CHEN Lijuan; YU Yeluo; LIU Chenlong; CHEN Yehai; WU Zilian; LU Xiaobao; LI Yaqing (Dianxin kexue)
In the space environment, visual sensors capture images with single colors, weak textures, and few feature points, making image stitching difficult. The Hessian matrix and scale space were constructed to obtain matching points through non maximum suppression, using Harris corner detection algorithm to construct feature point descriptors. RANSAC algorithm was used to filter the matching results and obtain the homography matrix for concatenation. In addition, satellite images were used in the experimental section to compare the processing performance of Harris corner detection algorithm with other algorithms. The results show that the Harris corner detection algorithm has better image stitching performance, and can be used to quickly stitch satellite images using the limited computing power of onboard processing units based on the Harris corner detection algorithm.